Brain volume in chronic ketamine users — relationship to sub-threshold psychotic symptoms and relevance to schizophrenia - Robert A. Chesters; Fiona Pepper; Celia Morgan; Jonathan D. Cooper; Oliver D. Howes; Anthony C. Vernon; James M. Stone (Psychopharmacology, 2022)
Rationale Ketamine may model aspects of schizophrenia arising through NMDA receptor activity deficits. Although acute ketamine can induce effects resembling both positive and negative psychotic symptoms, chronic use may be a closer model of idiopathic psychosis. Objectives We tested the hypotheses that ketamine users had lower brain volumes, as measured using MRI, and greater sub-threshold psychotic symptoms relative to a poly-drug user control group. Methods Ketamine users (n = 17) and poly-drug using controls (n = 19) were included in the study. All underwent volumetric MRI imaging and measurement of sub-threshold psychotic symptoms using the Comprehensive Assessment of At-Risk Mental State (CAARMS). Freesurfer was used to analyse differences in regional brain volume, cortical surface area and thickness between ketamine users and controls. The relationship between CAARMS ratings and brain volume was also investigated in ketamine users. Results Ketamine users were found to have significantly lower grey matter volumes of the nucleus accumbens, caudate nucleus, cerebellum and total cortex (FDR p < 0.05; Cohen’s d = 0.36–0.75). Within the cortex, ketamine users had significantly lower grey matter volumes within the frontal, temporal and parietal cortices (Cohen’s d 0.7–1.31; FDR p < 0.05). They also had significantly higher sub-threshold psychotic symptoms (p < 0.05). Frequency of ketamine use showed an inverse correlation with cerebellar volume (p < 0.001), but there was no relationship between regional brain volumes and sub-threshold psychotic symptoms. Conclusions Chronic ketamine use may cause lower grey matter volumes as well as inducing sub-threshold psychotic symptoms, although these likely arise through distinct mechanisms.